2023
DOI: 10.15537/smj.2023.44.2.20220793
|View full text |Cite
|
Sign up to set email alerts
|

The role of teleradiology during COVID-19 outbreak

Abstract: Objectives: To evaluate the role of teleradiology during the COVID-19 pandemic from Saudi radiologists' perspectives to improve the radiology quality service. Methods:A cross-sectional study was carried out in Saudi Arabia among radiologists working at local hospitals from October to November 2021. It contains 21 questions involved demographic information; general information on teleradiology services; and the impact of teleradiology during COVID-19. One-way ANOVA was used to compare demographic groups. Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…La teleradiología también juega un papel significativo en los departamentos de emergencias pediátricas, donde la evaluación de imágenes de teleradiología ha demostrado mejorar el manejo y la consulta de pacientes (Bucak et al, 2022). Durante la pandemia de COVID-19, la teleradiología ha sido fundamental para superar los efectos de los confinamientos y abordar la falta de personal y experiencia adecuados, destacando su papel crítico en situaciones de crisis (Al-Dahery et al, 2023;Pankhania, 2020).…”
Section: La Especialización En Radiologíaunclassified
See 1 more Smart Citation
“…La teleradiología también juega un papel significativo en los departamentos de emergencias pediátricas, donde la evaluación de imágenes de teleradiología ha demostrado mejorar el manejo y la consulta de pacientes (Bucak et al, 2022). Durante la pandemia de COVID-19, la teleradiología ha sido fundamental para superar los efectos de los confinamientos y abordar la falta de personal y experiencia adecuados, destacando su papel crítico en situaciones de crisis (Al-Dahery et al, 2023;Pankhania, 2020).…”
Section: La Especialización En Radiologíaunclassified
“…Sin embargo, se han señalado desafíos en el uso de la teleradiología durante la pandemia de COVID-19, particularmente relacionados con la naturaleza no sistemática de las búsquedas globales gratuitas, lo que puede presentar obstáculos para su implementación efectiva (Mbunge et al, 2022). No obstante, se ha reconocido la contribución positiva durante el brote de COVID-19, destacándose su capacidad para disminuir el riesgo de infección y la carga de trabajo (Al-Dahery et al, 2023).…”
Section: Introductionunclassified
“…Technological advancements in the past decade have significantly widened its scope, enabling the digital transmission of images from remote locations to teleradiologists anywhere in the country [ 2 ]. This capability has greatly enhanced the quality of care in these regions, especially highlighted during and after the COVID-19 pandemic [ 3 ].…”
Section: Editorialmentioning
confidence: 99%
“…While the expansion of teleradiology services undoubtedly enhances healthcare outcomes in remote areas, it is crucial to maintain the quality of radiological interpretations and continue attracting top talent to the field [ 3 ]. The trend of employing radiologists in India for reading international scans at lower reimbursement rates does not support this objective and can lead to job dissatisfaction, increased workloads, and burnout [ 6 ].…”
Section: Editorialmentioning
confidence: 99%
“…A study conducted in Saudi Arabia by Al-Dahery et al found that many radiologists believed that teleradiology was a useful tool for image interpretation, especially during the COVID-19 pandemic, which could enable decreasing the risk of infection and helping distribute the workload. 15 A deeper understanding is needed to explore any challenges associated with teleradiology practice and develop strategies to overcome them.…”
Section: Introductionmentioning
confidence: 99%